Anthropological Aspects of Problem Of God, Faith and Grace - Ozorowski, Edward (Studia Theologica Varsaviensia, 2020)
e arguments presented here can be qualified as a part of the more extensive problem concerning relations between the Christian religion and human nature. We have only limited ourselves to paying attention to the essential components of the religious phenomenon&Y. It seems, however, that in the context of all these theological theses and church rites, the question should be posed about how they arise from human existence as well as how they can serve it since only then would their fully anthropological value be fully manifested. What is more, one should refer to a religious phenomenon as such and consider Christianity in its context. Christian religion, in spite of its essential separateness from other religions, shares many common features with them. Christians, therefore consider important the philosophical question of whether religiousness defines man to the same extent as the category homo sapiens, homo socialis, homo faber, etc. does&_. e problem of the role that religion plays in human life is also significant. Many scholars, for example, emphasize the personality-forming role of religion and its role in maintaining man’s mental health;`. Man is then the point of reference when proving the raison d’être of the Christian religion. It is not enough to say that the Church comes from God, we must also justify that it is necessary for people. Similarly, the problem of verification of the Christian religion does not only consist in proving that the present-day Church comes from Christ and that in its historical duration it remains faithful to the will of its founder, but also in justification of the thesis that it represents the value necessary for people. Since according to the scholastic principle of verum, it can be considered ens and bonum at the same time. e latter is, however, an anthropological issue. Also dogmatic and moral theology, not to mention practical theology and theology of internal life, which by their very nature deal with man, is characterized by an anthropological attitude. We have already mentioned that contemporary Catholic theology is strongly inclined towards anthropology. It must be added here that the interests of dogmatics and moral theologians should not be limited to the mere interpretation of revealed truths about man, but should also take into account the confrontation of these truths with the experience of a man about himself. en the relevance and validity of dogmatic theorems will become clearer and indications of moral theology will become more convincing.